Comparison between endoscopic and laparoscopic removal of gastric submucosal tumor. (16th April 2018) - Abe, Nobutsugu; Takeuchi, Hirohisa; Ohki, Atsuko; Hashimoto, Yoshikazu; Mori, Toshiyuki; Sugiyama, Masanori
Abstract : Background and Aim: A retrospective study was conducted to compare two resection methods, namely, endoscopic resection (ER) procedures (endoscopic submucosal dissection [ESD], endoscopic muscularis dissection [EMD], and endoscopic full‐thickness resection [EFTR]) and laparoscopic resections (LR) (laparoscopic endoscopic cooperative surgery [LECS] and laparoscopic wedge resection). Methods: Seventy‐three patients who underwent ER ( N = 33: ESD, N = 4; EMD, N = 15; EFTR, N = 14) or LR ( N = 39: LECS, N = 16; wedge resection, N = 23) for gastric submucosal tumor (G‐SMT) smaller than 50 mm were included in this study. Patient/tumor characteristics and intra/postoperative factors were compared between the ER and LR groups. Results: The ER group had a significantly higher percentage of intraluminal growing type of tumor (100% vs 41%) and smaller tumor size (23 vs 33 mm) than the LR group. The ER group had a significantly shorter operative time (93 vs 145 min) and less blood loss (13 vs 30 mL) than the LR group. In the ER group, three patients who had tumors located on the anterior wall of the stomach required laparoscopic closure after EFTR because of difficulty in endoscopic closure of the gastric‐wall defect. Postoperative complication rates and duration of postoperative hospital stays did not differ between the two groups. Conclusions: ER may be technically feasible, safe, less invasive, and oncologically appropriate options for selected patients with the intraluminal growing type of G‐SMT smaller than 30 mm. EFTR may be more reasonable alternatives to LR in selected patients with a small G‐SMT located on the lesser curvature side.